Development of Pyrolysis Learning Media in New and Renewable Energy Courses - Muhamad Maulana Al Ghazali; Danar Susilo Wijayanto (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2026)
This study aims to develop a pyrolysis learning medium in the form of a practicum apparatus and an interactive e-module to support learning in the Renewable Energy course in the Mechanical Engineering Education Program, Faculty of Teacher Training and Education, Universitas Sebelas Maret. This research is motivated by the limited availability of practical learning media, which has caused pyrolysis learning to be predominantly theoretical. The research employed a Research and Development (R&D) approach using the ADDIE development model. Media validation was conducted by subject-matter experts and media experts, while user testing involved 13 students. Data were collected using expert validation questionnaires, pretest–posttest instruments, user trial questionnaires, and interviews. The validation results indicated a very high level of feasibility, with scores of 95% from subject-matter experts and 81.76% from media experts, while user testing showed a feasibility level of 82.4%. The developed learning media helped students understand the pyrolysis process in a visual and applicative manner and increased their engagement and conceptual understanding. Therefore, this study contributes to the enhancement of Renewable Energy learning through the provision of contextual pyrolysis practicum media and has important implications for improving the quality of technical and vocational education by integrating practice-based and technology-enhanced learning.